GE_GERICHTE P/7948/2018 vom 8. August 2018 - GE Cour de justice (2018)
CONTRAVENTION ; ORDONNANCE PÉNALE ; OPPOSITION TARDIVE ; PRESCRIPTION ; CLASSEMENT DE LA PROCÉDURE | CPP.329.al4; CPP.356.al2; CPP.354.al1; CP.97.al3